Um sistema em fluxo para preparação de misturas gasosas e análise screening de GNV e GLP com respeito ao conteúdo de metano e propano usando espectrometria NIR e quimiometria - Dantas, Hebertty Vieira (2014)
Concern about environmental problems triggered the search for new sources of energy and consequently caused an increase in the use of gaseous fuels such as natural gas (NG) and liquefied petroleum gas (LPG). Given this reality, there is growing demand for quality monitoring and supervision of this type of fuel. This paper proposes a flow system for the screening of samples of LPG and NG by near infrared spectrometry (NIR) analysis in order to verify the quality of these fuels in relation to its major concentration of hydrocarbons, propane and methane, respectively. For this, one spectrophotometric flow cell for gas, seven NG containers collectors and one flow system for injection and mixture of gases, as well as its automation (SAIMG) and building management software (GasMixer) were developed. The gas handling equipment and systems for flow enabled the development of SPA-LDA and SIMCA models for screening analysis of samples of LPG and NG. The classification models were constructed and tested with commercial samples that have been previously grouped and analyzed by gas chromatography. Adulterated NG mixtures with nitrogen, compressed air, ethane and lighter fluid were also created. LPG samples were grouped into two different classes depending on the concentration of propane, which have been termed "rich LPG" and "poor LPG" The NG samples were analyzed according to the specified limit for the concentration of methane, which resulted in negative cases ( NG -) and positive (NG +) when they are considered respectively higher or lower than the limits set limit. The results showed that the screening analysis was efficient and robust, reaching 100% accuracy compared samples of LPG and NG test. In addition, the automation of the flow system optimizes all stages of the analysis and enhances their use in future applications